TINJAUAN KRIMONOLOGI EKSPLOITASI SEKSUAL PADA ANAK - Nur Wahid Musaddiq (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
Sexual exploitation of children is a violation of children in the form of sexual violence committed by adults by giving rewards to children, or a third person, or other people who make children treated as sexual and commercial objects. This is forced labor and modern slavery of children because children often experience physical violence and trauma. Factors that cause sexual exploitation of children in Makassar City are environmental factors, technological factors and factors, economic factors, lack of understanding of religion and prevention efforts are carried out in two ways, namely pre-emptive, preventive and repressive measures. Recommendations that the government and the whole community participate in preventing sexual exploitation of children. Efforts that can be done by the community is if there is anything suspicious and should be suspected as a crime of sexual exploitation, the community must report to the authorities so that it can be followed up.